Knowledge and attitudes towards dietary fibers - romania vs other european countries - Tarcea, M. (2017)
Aim: The aim of our study was to evaluate the Romanian’s knowledge and attitudes regarding dietary fibers compared with other European countries. Materials and methods: We made a cross-sectional survey (part of multinational project from CI&DETS Research Centre, Instituto Politecnico Viseu, Portugal, with reference PROJ/CI&DETS/2014/0001) based on a questionnaire applied in 2015, over 670 Romanian consumers, focused on the attitudes and knowledge towards ingestion of foods rich in fibers. We used the software SPSS for statistics. Results: Our results showed that the knowledge about dietary fibers and also the ingestion of food products rich in fibers were low. The female participants ate more whole grains and fruits than males and pay more attention to food labelling, the Romanian people prefer to stay and eat home than at restaurants especially in rural areas, and the knowledge about fiber’s benefits was significantly related to high education and urban location. Comparing to other European countries, Romania had the highest level of knowledge about dietary fibers definition followed by Portugal, Turkey and Hungary, but the lowest regarding the fibers importance for health after Macedonia, Turkey and Latvia. Conclusion: We sustain the needs for more efficient community interventions and proper information about the importance of dietary fibers for our health and also for the dissemination of the nutritional standards among Romanian population.